Pipe clogging in the fertilizer industry, opportunities and challenges for computer vision. Issue 2 (2020) - Dias, Jovania; Duarte, Marta; Coch, Victor; Duarte, Nelson; Oliveira, Vinicius; Drews, Paulo; Botelho, Silva
Abstract: In the context of industry 4.0 where the use of new technologies is required to meet productivity and profitability demands, this paper addresses 3D scanning, thermal imaging and computer vision to identify pipe clogging caused by waste accumulation in the fertilizer industry. This paper presents a study using thermal images and the use artificial neural network to model the waste distribution in industrial pipes.